INTERNATIONAL INVESTMENT ACTIVITIES BETWEEN UKRAINE AND THE EUROPEAN UNION - NADVIRNIANSKYI, Yulian (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines approaches to the study of international investment policy in Ukraine and ways of further cooperation with the European Union. The main approaches are shown in the genesis of this problem. It is emphasized that the modern conduct of international investment activity is closely related to the state programs of Ukraine, the EU and the countries of the world as a whole. Separate areas of international investment support are substantiated. At the same time, it is believed that European investment support is an important tool for sustainable development of the state and ensuring its food security. However, in modern conditions, the issue of the organization of investment support for the country's economy requires a new approach, improvement of the considered support programs through active measures at the state level, introduction of new financial and credit structures. It is emphasized that during the organization and conduct of close cooperation between Ukraine and the EU, as well as during the development of measures to improve the organizational and economic mechanism of investment activity, it is necessary to take into account the peculiarities of the investment climate, without which it is impossible to achieve a high level of the country's economic potential.
Keywords: international investment activity; European Union; investment support; international cooperation